2021
DOI: 10.1080/02607476.2021.1942804
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ motivation to participate in continuous professional development: relationship with factors at the personal and school level

Abstract: Teachers' motivation to participate in professional learning is a significant factor in explaining the effectiveness of continuous professional development programmes. The present study investigated how factors at teachers' personal and school levels are related to their motivation to participate in professional learning activities. A questionnaire was completed by 472 Chinese teachers. Multivariate analysis revealed that several factors at the teacher level (teachers' prior experience with learning activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 45 publications
1
29
1
Order By: Relevance
“…This was somewhat different from the study conducted by Zhang et al (2021) in which the statistics showed a significant association between teachers' teaching experience and autonomous motivation. It was stated that teachers with more teaching experience were less autonomously motivated for professional learning activities.…”
Section: Levels Of Tefl Teachers' Motivation For Continuing Professional Developmentcontrasting
confidence: 95%
See 3 more Smart Citations
“…This was somewhat different from the study conducted by Zhang et al (2021) in which the statistics showed a significant association between teachers' teaching experience and autonomous motivation. It was stated that teachers with more teaching experience were less autonomously motivated for professional learning activities.…”
Section: Levels Of Tefl Teachers' Motivation For Continuing Professional Developmentcontrasting
confidence: 95%
“…The main reason for this discrepancy possibly lies in the programs designated to the research. In the study of Zhang et al (2021) , the professional program only referred to a specific educational program refining teachers’ pedagogical strategies. Teachers with more teaching experience may be less in favor of interactions about their subject domain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That many teachers are sustained in their motivation by and continue their learning through the notion of teaching as an intellectual activity has been a recurring theme through the pages of JET (see e.g. Murray et al 2009;Tang, Wong, and Cheng 2015;Glutsch and König 2019;Zhang, Admiraal, and Saab 2021).…”
Section: Teachers' Learning and Knowledge: Motivation And Self-efficacymentioning
confidence: 99%